Psychological Analysis of Public Behavior and Perception in Waste Burning Behavior - Hadis, Nur Athirah (Faculty of Psychology Sunan Gunung Djati Islamic University of Bandung, 2025)
Waste burning remains a common practice in many communities despite its negative impacts on health and the environment. This topic was chosen due to its urgency in the context of air pollution, particularly following the 2022 fire at the Antang landfill in Makassar, which highlighted weaknesses in waste management systems. This study aims to explore how low risk perception and strong social norms are associated with the persistence of waste burning behavior. This research employed a qualitative approach with a phenomenological method, involving five informants consisting of both perpetrators and those affected by waste burning. Data were collected through in-depth interviews and participatory observation, and analyzed using thematic techniques. The findings indicate that waste burning behavior is influenced by habits, limited waste collection services, and social norms that support the practice. Although the community is aware of health risks such as respiratory problems, stress, and decreased quality of life, the lack of alternative waste management methods reinforces this behavior. In conclusion, waste burning practices are primarily driven by psychological factors and inadequate environmental conditions. This study recommends improving waste management services, increasing public education about pollution hazards, and strengthening social norms that encourage environmentally friendly practices.